Innovation in practice: mobile phone technology in patient care - Blake, Holly (Mark Allen Healthcare, 2008)
Mobile phones are becoming increasingly important in everyday life and now in healthcare. There has been a steady growth of information and communication technologies in health communication and technology is used progressively in telemedicine, wireless monitoring of health outcomes in disease and in the delivery of health interventions. Mobile phones are becoming an important method of encouraging better nurse-patient communication and will undoubtedly increase in application over coming years. This article presents recent developments and applications of mobile technology for health promotion and patient-monitoring in chronic disease.